2016
DOI: 10.20944/preprints201610.0028.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mercury Exposure and Heart Diseases

Abstract: Environmental contamination has exposed humans to various metal agents, including mercury. It has been determined that mercury is not only harmful to the health of vulnerable populations such as pregnant women and children, but is also toxic to ordinary adults in various ways. For many years, mercury was used in a wide variety of human activities. Nowadays, the exposure to this metal from both natural and artificial sources is significantly increasing. Recent studies suggest that chronic exposure, even to low … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 41 publications
0
22
0
2
Order By: Relevance
“…A recent review suggested that mercury cause neurologic disorders [ 9 ], cardiovascular disease [ 10 ], and asthma in children [ 11 ]. In addition to evidence of mercury effects on various organs, some animal studies have suggested that acute mercury exposure can damage the liver [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review suggested that mercury cause neurologic disorders [ 9 ], cardiovascular disease [ 10 ], and asthma in children [ 11 ]. In addition to evidence of mercury effects on various organs, some animal studies have suggested that acute mercury exposure can damage the liver [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…An expert panel convened by the US Environmental Protection Agency in 2011 concluded that methylmercury is directly linked to acute myocardial infarction and to increases in cardiovascular risk factors such as oxidative stress, atherosclerosis, decreased heart rate variability, and to a certain degree, hypertension [ 76 ]. Likewise, a 2017 systematic review found that methylmercury enhances production of free radicals resulting in a long-lasting range of effects on cardiac parasympathetic activity that increase risk for hypertension, myocardial infarction, and death [ 77 ]. Further research has confirmed these findings [ 78 79 ].…”
Section: Impacts Of Ocean Pollution On Human Healthmentioning
confidence: 99%
“…Human exposure to metal ions, including Hg(II), can occur during occupational activities, mainly through inhalation and dermal routes in mining and industry, and over a lifetime, from water and food consumption and exposure to soil, dust and air [ 4 , 5 ]. Long-term consumption of drinking water contaminated with Hg(II) can be associated with increased risk of cancers, reproductive problems, detrimental effects on the human brain, blood circulation, immune and reproductive systems and cardiovascular disease [ 2 , 6 , 7 ]. Therefore, to minimize these risks, the United States Environmental Protection Agency (USEPA) has set the maximum permissible limit of 2 µg L −1 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%